Effect of production system on physical–chemical, antioxidant and fatty acids composition of Longissimus dorsi and Serratus ventralis muscles from Iberian pig - Tejerina, D; García-Torres, S; Cabeza de Vaca, M; Vázquez, F M; Cava, R (Food Chemistry, 2012)
The effect of three production systems of Iberian pigs namely Montanera (free-range system and feeding based on acorns and grass), Recebo (free-range system and nutrition based in combination of acorns, grass and mixed feeds) and Intensive (conﬁnement with mixed feeds) on some quality traits of Longissimus dorsi (LD) and Serratus ventralis (SV) muscles were studied. Muscles from pigs raised in the Montanera system showed signiﬁcantly higher CIE L ⁄ , a ⁄ and b ⁄ values and higher haem pigment content than those from Intensive system. Similarly, muscles from pigs raised in the Montanera system had signiﬁcantly higher contents of a and c-tocopherol and phenolic compounds contents and higher lipophilic and hydrophilic activity antioxidant than those from pigs raised in the Intensive system. Fatty acids proﬁles from Montanera pigs had signiﬁcantly higher monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids and lower saturated fatty acids (SFA) than those from pigs raised in the Intensive system. In relation to muscle effect, LD showed lower intramuscular fat (IMF), a-tocopherol, phenolic compounds, lipid oxidation and PUFA, but higher MUFA than SV.
Keywords: antioxidant; fatty acids; Iberian pigs; Montanera

Study of variability in antioxidant composition and fatty acids profile of Longissimus dorsi and Serratus ventralis muscles from Iberian pigs reared in two different Montanera seasons. - Tejerina, D; García-Torres, S; de Vaca, M Cabeza; Vázquez, F M; Cava, R (Meat science, 2012)
This investigation was designed to evaluate the effects of variations in antioxidant and fatty acids composition of acorns and grass from two Montanera (free-range system and feeding based on acorns and grass) seasons (2006/07 and 2007/08) on the antioxidant composition and fatty acids profile of m. Longissimus dorsi (LD) and m. Serratus ventralis (SV) from Iberian pigs reared under these Montanera seasons. Acorn and grass composition was affected by Montanera season and consequently, LD and SV muscles showed different contents of α-tocopherol, total phenols, hydrophilic and lipophilic antioxidant activity and fatty acid profile, according with the composition of acorns and grass ingested. Results suggest a lack of uniformity in meat quality between different seasons. This could be due to the variable nature of extensive pig production as reflected in the variability in the composition of the diet (acorns and grass).
Keywords: acorns; diet composition; Grass; Iberian pigs; meat; Montanera

Water-holding capacity and instrumental texture properties of m. Longissimus dorsi and m. Serratus ventralis from Iberian pigs as affected by the production system - Tejerina, D; García-Torres, S; Cava, R (Livestock Science, 2012)
Meat from Iberian pigs had a high quality and an important acceptance for consumers, but is affected enormously by production conditions. So, in this study, ninety Iberian pigs were randomly allotted into three batches – Montanera (free-range rearing and fed on acorns and grass), Intensive (conﬁnement rearing and fed on concentrate) and Recebo (free-range rearing fed on acorn, grass and concentrate) – in order to characterize the inﬂuence of the production system on water holding capacity (WHC), drip loss, thaw loss and cook loss and instrumental texture traits of m. Longissimus dorsi and m. Serratus ventralis. Muscles from pigs raised in Montanera had greater WHC and lower water losses after thawing than those from Intensive system. Instrumental texture analysis showed that muscles from Montanera pigs had different characteristics as determined by instrumental Texture proﬁle analysis (TPA) and with most resistance to cutting of the muscle ﬁbres Warner–Bratzler (W–B). In all the cases, however, the type of muscle showed a different behaviour on water loss and rheological properties. So, these results suggest that meat quality of Iberian pig is highly inﬂuenced by the production system and type of muscle studied.
Keywords: iberian pig; Instrumental texture; Muscle; Production system; Water-holding capacity

Extensively reared Iberian pigs versus intensively reared white pigs for the manufacture of liver pâté. - Estévez, M; Morcuende, D; Ramírez, R; Ventanas, J; Cava, R (Meat science, 2004)
Physico-chemical characteristics and quality traits of the raw ingredients (muscle cuadriceps femoris, liver and adipose tissue) and the pâtés made from extensively reared Iberian pigs and intensively reared white pigs, were evaluated. The differences found between muscles, livers and adipose tissues from Iberian and white pigs influenced the characteristics of the pâtés. Compared to pâtés from white pigs, pâtés from Iberian pigs had a higher content of heme iron (27.5 μg/g vs 11.5 μg/g; p<0.05) and lower content of non-heme iron (27.5 μg/g vs 33.7 μg/g; p<0.05). Pâtés from Iberian pigs exhibited a darker colour (L (∗):18.6 vs 15.9, p<0.05) with less redness (a (∗) values: 9.1 vs 11.3; p<0.05) and yellowness (b (∗) values: 13.1 vs 14.8, p<0.05). Thus, pâtés from white pigs had higher values of chroma (18.6 vs 15.9, p<0.05) and smaller values of hue (52.5 vs 55.2, p<0.05) that those from Iberian pigs' pâtés. In fatty acid composition, pâtés from white pigs had higher proportions of SFA (37.9% vs 32.8%, p<0.05) and PUFA (14.4% vs 9.6%, p<0.05) than pâtés from Iberian pigs and lower percentages of oleic (53.4% vs 43.6%, p<0.05) and total of MUFA (57.5% vs 47.6%, p<0.05). Pâtés from Iberian pigs had a lower n-6/n-3 values (13.2 vs 17.2; p<0.05).
Keywords: Extensive; fatty acids; Iberian pigs; Instrumental colour; Iron; liver p; liver paté; White pigs

Prediction of the feeding background of Iberian pigs using the fatty acid profile of subcutaneous, muscle and hepatic fat. - Ruiz, J; Cava, R; Antequera, T; Martín, L; Ventanas, J; López-Bote, C J (Meat science, 1998)
Thirty Iberian pigs weighing 95 kg were randomly distributed into three groups of 10 animals each and fattened in three traditional management systems ['montanera' (MO), fed extensively on acorns, 'cebo' (CE) fed on a commercial diet and 'recebo' (RE), fed on acorns and a commercial diet]. Fatty acids from the Masseter muscle, lard and liver were analysed. In the lard, fatty acid profiles from MO and RE pigs presented minor differences; however, in the liver, RE pigs showed differences to MO pigs in most of the fatty acids studied. This suggests that the muscle and especially the liver fatty acid profile reflects the feeding regime during the last phase of feeding, while the lard reflects longer term differences.
Keywords: Fatty acid profile; Feeding regime (voyant); iberian pig

Influence of finishing diet on fatty acid profiles of intramuscular lipids, triglycerides and phospholipids in muscles of the Iberian pig. - Cava, R; Ruiz, J; López-Bote, C; Martín, L; García, C; Ventanas, J; Antequera, T (Meat science, 1997)
Thirty Iberian × Duroc pigs allotted in groups of ten animals were fed in three traditional different management systems ('Montanera' (MO), fed on acorns; 'Recebo' (RE), fed on acorns and a commercial diet; and 'Cebo' (CE), fed on a commercial diet). Masseter muscle was obtained to evaluate the influence of management system on fatty acid (FA) composition of lean. The FA composition of the intramuscular total lipids, triglyceride (TG) and phospholipid (PL) fractions was evaluated. Muscle from MO pigs had greater quantities of monounsaturated fatty acids (MUFA) in the total lipids, triglyceride and phospholipid fractions than the other feedings. The percentage of saturated fatty acids (SFA) of i.m. total lipids and TGs increased (P < .05) with duration of feeding on RE and CE, from 35.13-35.10% in MO pigs to 37.47-37.84% in RE pigs and 39.98-41.11% in CE pigs. PLs from RE and CE pigs contained more C(18:2) and C(20:4) and less C(18:1) than MO pigs.
Keywords: Fatty acid profile (PG); Feeding system; iberian pig